Evaluation of myofibroblasts in oral submucous fibrosis and oral squamous cell carcinoma: The pathogenesis and correlation - Piyush Gandhi; Umesh Chandra Prasad (Wolters Kluwer Medknow Publications, 2017)
Background: Oral submucous fibrosis (OSMF) is a chronic debilitating disease of the oral cavity having premalignant potential and unclear pathogenesis. Recently, myofibroblast has been postulated to play an important role in its pathogenesis and in the process of carcinogenesis. The purpose of this study was to evaluate and compare the presence of myofibroblasts in normal mucosa, different grades of OSMF, and oral squamous cell carcinoma (OSCC). Materials and Methods: The present in vitro cross-sectional descriptive study sample consisted of three groups, including 40 OSCCs, 40 OSMF, and 10 sections of normal oral epithelium taken as control group. Alpha-smooth muscle actin was used to identify myofibroblasts using immunohistochemical technique. P < 0.05 was taken as statistically significant. Results: The presence of myofibroblasts was significantly higher in OSMF cases when compared with normal epithelium specimens. The presence of myofibroblasts was significantly higher in OSCC compared to OSMF cases. A significant difference was not observed between the different grades of OSCC. Conclusion: These findings favor the possibility that OSMF actually represents an abnormal healing process in response irritation caused by areca nut. A significant increase in myofibroblasts in OSCC as compared to OSMF also highlights the possible role it may play in the malignant transformation of OSMF.